The impact of electronic banking on customer satisfaction in commercial banks - Ayebare Dyline (Uganda Christian University, 2024)
This paper therefore explores the effect of electronical banking on customer satisfaction in commercial banks, a case study of Stanbic Bank Uganda limited (SBU). The population of the study were customers/clients of Stanbic bank which were estimated to be seventy 70 respondents, while the sample size was fifty-two 52 respondents determined using the Krejcie and Morgan Table. Descriptive and quantitative research designs were adopted for this research, with the purpose of the non-random sampling technique. Data was collected using both interviews and questionnaires on Stanbic Bank customers. Data was analyzed using calculators and a statistical package for social sciences (SSPS). Results indicated that indeed, interbanking operations have been a great help in effecting transactions between and among banks for the satisfaction of customers. Challenges were also noted to arise in the course of interbanking mainly in the areas of security and customer service. Whereas 86.9% of customers felt that the e-banking platform was user-friendly, a paltry 19.4% showed confidence in its security, hence showing a yawning gap in the area of trust, and customer support services were rated as much less satisfactory, where a higher proportion, 57.4%, expressed dissatisfaction with the way they were helped by the bank. The results of this study, therefore, reveal that, although the use of Stanbic Bank's e-banking services is driven by ease of use, convenience, and a variety of services offered, concerns on security, customer support. This conclusion provided the needed lessons that would be applied by commercial banks towards an improved e-banking service considering customer satisfaction, and established the role of digital banking in modern financial institutions. The strategic recommendations were to guide areas for improvement with a view to sustaining the competitive advantage. Improvement in customer relationships through the development of customer satisfaction and loyalty needs the bank's focus to shift toward enhancing the security protocols with better encryption techniques while making customer support more responsive and transparent with respect to the levied fees.